Experimental and natural infestations of Sarcoptes scabiei in goats and sheep - AHMED, M A; BASU, A; ANSARI, M Z (The Indian Journal of Animal Sciences, 2013)
Clinical studies, at weekly intervals, in goats and sheep in experimental and natural infestation of Sarcoptes scabiei revealed that tho lesions were more diffuse and generalized in goats, and were localized in patches, espcctially at the margin of cars and planum nasale in sheep. Both the hosts exhibited similar clinical manifestations dul.!to natural contact and cxpcrnncntal infestation with mites of homologous host origin, but the severity uf infestation Was less in naturally infested animals. Sarcoptes scabiei, both of goat origin and sheep origin, were strictly host specifie.